The comparison of ambulatory activity among people living in different regions, and relationship with BMI in Pohnpei state, the Federated States of Micronesia: Cross-sectional study. (December 2020) - Sakai, Moeno; Nakazawa, Minato; Abraham, Delpihn
Abstract: Aims: To clarify people's ambulatory activity and the relationship with BMI among people living in different regions with different lifestyles within the Federated States of Micronesia (FSM), where has been experiencing a rapid increase in the obesity population. This study is the first study which quantitatively explores physical activity in the country. Methods: A cross-sectional study was conducted from July to September in 2019. 50 participants were recruited from Kolonia (urban area in a main island) and Mand (rural area in the main island), and 2 participants in Kolonia dropped out, while 34 participants were recruited in Pingelap (outer island). BMI was calculated based on anthropometric measurements. Ambulatory activity was measurement by pedometer-determined steps/day. Results: Average steps/day varied among the three regions (4179 to7282 to 9252 in males, 3714 to 5087 to 8069 in females, Kolonia to Mand to Pingelap, respectively, P < 0.001). A linear mixed model showed a statistically inverse correlation with steps/day after adjustment of the differences in the relationship of each region (β = −0.436, 95% CI = -0.814 to −0.052). Conclusion: Urbanization might decrease ambulatory activity within FSM. Increasing ambulatory activity can decrease BMI, which might be one of the clues to solve the increasing prevalence of obesity. Highlights: There was a statistical regional difference in ambulatory activity within FSM. There was an inverse correlation between ambulatory activity and BMI. Increasing 1000 steps/day decrease Body Mass Index by 0.436 kg/m 2 .